2017
DOI: 10.1016/j.apenergy.2017.08.207
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of indoor parameters an subjective responses of building occupants in a hot region of Indian ocean; a case of Madagascar island

Abstract: The 80% of voters found their environment comfortable. • In all the studied places, during both seasons, no people voted "cold environment". • The 52.0% of male were satisfied of their thermal environment. • An ANOVA analysis shown that the voters are feeling more comfortable in hospitals. • No great differences between males and females in their thermal sensations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 34 publications
1
22
3
Order By: Relevance
“…Energy demand increased to 19.6% between 1975 and 2000. These results are similar at those estimated by Christenson et al [41] , who showed that the heating degree-days were reduced by 11-18% during 1901-2003, but reached 1387% between 1975 and 2085. Some researchers showed that the extent of reduction in heating and increase in cooling varies from one region/climate to another and depends very much on the prevailing local weather conditions and energy efficiency measures [25][26][27] .…”
Section: Energy Demand Of Buildings 321 Time-scale Of the Past And supporting
confidence: 92%
See 2 more Smart Citations
“…Energy demand increased to 19.6% between 1975 and 2000. These results are similar at those estimated by Christenson et al [41] , who showed that the heating degree-days were reduced by 11-18% during 1901-2003, but reached 1387% between 1975 and 2085. Some researchers showed that the extent of reduction in heating and increase in cooling varies from one region/climate to another and depends very much on the prevailing local weather conditions and energy efficiency measures [25][26][27] .…”
Section: Energy Demand Of Buildings 321 Time-scale Of the Past And supporting
confidence: 92%
“…Vulnerabilities of climate change varied according to geographic position. Nematchoua et al, in a study carried out in Cameroon, found rather that the maximum temperature tends to increase faster in the dry season than in the rainy season [41] . It's important to note that the consequences of this calamity are visible and vary from one country to another.…”
Section: Case Of Variation In the Annual Maximum Temperaturementioning
confidence: 93%
See 1 more Smart Citation
“…Thereafter, a differential analysis between residences was made. Such as, in several in-depth statistical types of research (Nematchoua et al,2017), the t-test was used in this part, all statisticalanalyseswere carried out with a 95% confidence level (CL), which was considered the level of significance equal to 5%. In both residences, a meticulous analysis of ten environmental impacts was applied at two-phases (construction and exploitation), as showed on table4.…”
Section: Figure8shows a Comparison Of Environmental Impacts From The mentioning
confidence: 99%
“…To calibrate this model, we compared the different simulated and measured values of a building typically encountered in Madagascar [23], by calculating the linear correlation coefficient (R 2 ) to analyze the margin of error. The literature shows that the error is negligible if the correlation coefficient obtained is around of ±1.…”
Section: Calibration Of Modelmentioning
confidence: 99%